Inpatient Geriatric Pain Management Discussion Cases - Angela Botts (Association of American Medical Colleges, 2009)
Abstract This module includes discussion cases designed to enhance small-group learning for multidisciplinary house-staff regarding inpatient geriatric pain management. The content is arranged into three patient-based cases focusing on pain management and assessment in demented elders; postoperative pain management and delirium; and neuropathic pain management. Pre- and postassessments evaluate learner knowledge gains. Academic hospitalists within Beth Israel Deaconess Medical Center have demonstrated the ability to use these cases during teaching rounds with house staff. Informal feedback from house staff has been very positive and they have preferred using these cases for discussion compared to more traditional didactic sessions. The Inpatient Geriatric Pain Management Discussion Cases are a valuable resource in teaching multidisciplinary residents how to optimally assess and treat pain in elders. This topic has particular significance as there is a twofold increase in painful conditions among elders as compared to younger individuals. In addition, pain in elders is often underrecognized and poorly treated with significant associated adverse outcomes. These cases have proven effective in increasing knowledge among internal medicine house staff regarding pain management issues in hospitalized elders.